Application of motor rehabilitation programs in the normalization of the psycho-emotional sphere of patients with Parkinson’s disease - Voloshina Наталія; Bogdanova Ірина; Voloshyn-Gaponov Іван; Fedoseev Сергій; Tereshchenko Людмила; Bohdanova Таїсія (Psychosomatic Medicine and General Practice, 2022)
In order to study the effectiveness of the motor rehabilitation program for Parkinson’s disease patients, 48 ​​patients who underwent a course of motor rehabilitation using the phenomenon of paradoxical kinesia and subsequently followed the rehabilitation recommendations in different ways were clinically examined. It was found that patients who underwent an additional online rehabilitation program and subsequently followed the rehabilitation recommendations demonstrated a significantly better state of the psycho-emotional sphere compared to patients who underwent online rehabilitation, but did not follow the recommendations, and patients who did not undergo online online rehabilitation and did not follow the recommendations. The indicators in these groups were, respectively: on the HDRS scale: 10.18±3.64 points, 14.56±1.82 points and 17.87±3.27 points, respectively, on the A. Beck scale: 7.18±3 .94 points, 11.63±3.59 points, 20.93±13.43 points; according to the HADS depression scale: 9.06±2.88 points, 12.88±1.67 points, 15.13±2.33 points; according to the HARS scale: 18.41±4.29 points, 21.38±3.56 points, 29.40±8.12 points; according to the HADS anxiety scale: 9.06±2.16 points, 11.06±1.88 points, 13.73±3.17 points; reactive anxiety: 34.47±6.29 points, 39.63±4.98 points, 44.93±6.83 points; personal anxiety: 38.71±10.00 points, 40.38±5.92 points, 50.80±10.90 points; somatization: 0.68±0.19 points, 0.93±0.27 points, obsessive-compulsive symptoms: 0.44±0.73 points, 1.38±0.73 points, 1.89±0.46 points; interpersonal sensitivity: 1.22±0.32 points, 1.63±0.38 points, 1.96±0.26 points; depression: 1.46±0.53 points, 1.98±0.56 points, 2.67±0.78 points; anxiety: 1.89±0.35 points, 2.32±0.39 points, 2.68±0.27 points; hostility: 0.00±0.00 points, 0.03±0.13 points, 0.25±0.20 points; phobic anxiety: 0.55±0.31 points, 0.91±0.36 points, 1.19±0.32 points; psychoticism: 0.44±0.22 points, 0.51±0.26 points, 0.69±0.27 points. Full implementation of the program and recommendations also contributed to the improvement of quality of life indicators in all key areas.